Influencing how young learners think. A case study. - Kececioglu, Ellen Marie (2018)
This case study is an exploration into how students thinks about their learning, specifically student choice, motivation and mindset. A small sample of same age students from grade one were observed over a period of four weeks during a writing class. This class was co taught alongside the homeroom teacher. Findings suggest that participant choice and relationships had a significant role with regard to how students thought about writing. Students were confident in their knowledge of how they learned and what impacted their learning both constructively and adversely. Being creative in the writing process was impacted by the relationships of peers though views varied. The language used by the educator in the classroom would appear to have a strong influence on student mindset with regard to learning. Data indicates that when feedback is incorporated into teaching young students they view it as a natural part of their learning journey. This investigation contributes to the overall understanding of how learning may be influenced to create an understanding that it takes effort and an open mind to become proficient in any area.